A type II cannabis extract and a 1:1 blend of Δ(9)-tetrahydrocannabinol and cannabidiol display distinct antinociceptive profiles and engage different endocannabinoid targets when administered into the subarachnoid space - Benredjem, Besma; Pineyro, Graciela (Frontiers in Pharmacology, 2023)
Cannabis extracts are being increasingly used to mitigate chronic pain. Current guidelines for their prescription rely on Δ 9 -tetrahydrocannabinol (THC) and cannabidiol (CBD) content as well as the ratio of these major cannabinoids present in the blend. Here we assessed whether these descriptors were representative of product effectiveness to produce a desired outcome such as analgesia. To address the question, the study used a rat model of diabetic neuropathy and assessed the reduction in mechanical allodynia following intrathecal injection of pure THC, pure CBD, a 1:1 mix of these compounds and a "balanced" chemotype II cannabis extract. Engagement of endocannabinoid targets by different treatments was investigated using CB1 (AM251) and CB2 (AM630) receptor antagonists as well as a TRPV1 channel blocker (capsazepine). Antinociceptive responses induced by an equivalent amount of THC administered in its pure form, as a THC:CBD mix or as a "balanced" extract were distinct. Furthermore, the 1:1 THC:CBD mix and the balanced extract had not only different response profiles but their relative engagement of CB1, CB2 receptors and TRPV1 was distinct. These findings indicate that antinociceptive responses and targets engaged by blended cannabinoids are composition-specific, and cannot be simply inferred from THC and CBD contents. This information may have implications in relation to the way medicinal cannabis products are prescribed.